(3GdgGQhfjI aj GdJUQjas - (3fLe GdOjf YeQ Hf YjSi Hf ESeGYjd GdgQhi,J (B700 (3g` s ((3Ydi Hf WhZGf s)
(3ChdgG (B:s
(3hHYO agPG eNJUQ ai GdJUQja ai SJI aUhd s
(3BNQgG (B:s
(3aYdi fMh SdajJg aGSJdbi , JeJ GdebOeI GdgGQhfjI s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2027s
Keywords: (3GdUQas